The use of mesh implants in vaginal prolapse surgery: Position statement and recommendations of the South African Urogynaecology Association - Etienne Henn (South African Medical Association, 2014)
This is the 2014 updated guideline and position statement from the South African Urogynaecology Association on the use of transvaginal mesh for the surgical correction of pelvic organ prolapse.